La letra-sinthome o el sentido del ser en Joyce (2012)
ABSTRACT: This text is dedicated to the analysis of the following phrase, spoken by Lacan: “The word, it’s clear, is defined as being the only place where being has meaning. The sense of being presides over having, which excludes epistemic muttering.” The article demonstrates in what way a sinthome is constructed and what function it fulfills for the subject.